2016
DOI: 10.3897/zookeys.601.7704
|View full text |Cite
|
Sign up to set email alerts
|

Kankuamo, a new theraphosid genus from Colombia (Araneae, Mygalomorphae), with a new type of urticating setae and divergent male genitalia

Abstract: A new monotypic Theraphosidae genus, Kankuamo Perafán, Galvis & Pérez-Miles, gen. n., is described from Colombia, with a new type of urticating setae. These setae differ from others principally by having a small distal oval patch of lanceolate reversed barbs. Males of Kankuamo gen. n. additionally differ by having a palpal bulb organ very divergent from all known species, with many conspicuous keels dispersed across the median tegulum to the tip, mostly with serrated edges. Females differ by having spermatheca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…None of the previously described types displayed much morphological similarity with type II beyond the position criterion (Bertani and Guadanucci, 2013). However, type VII shares several characteristics with type II setae (Perafán et al, 2016). It has even been suggested that urticating setae in Kankuamo and Type II share a similar "direct contact" method -i.e.…”
Section: Morphology Meets Phylogenomics: Insights Into the Evolution mentioning
confidence: 94%
See 2 more Smart Citations
“…None of the previously described types displayed much morphological similarity with type II beyond the position criterion (Bertani and Guadanucci, 2013). However, type VII shares several characteristics with type II setae (Perafán et al, 2016). It has even been suggested that urticating setae in Kankuamo and Type II share a similar "direct contact" method -i.e.…”
Section: Morphology Meets Phylogenomics: Insights Into the Evolution mentioning
confidence: 94%
“…In a long-range defense mechanism loosely known as "hair flicking" or "bombardment" (Fig 1a), many Neotropical species will use their legs to slough off these setae from their opisthosoma and actively disperse them into the air when a threat is perceived (Cooke 1972;Bertani and Guadanucci, 2013). Other species opt for an active "direct contact" approach against potential threats, in which they seek to press them onto the target (after Cooke 1972;Bertani and Guadanucci, 2013;Perafán et al, 2016). Consequently, urticating setae have been known to induce painful symptoms in humans (Zilkens et al, 2012;McAnena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Theraphosidae Thorell, 1869 are composed by 974 species and 144 genera (World Spider Catalog 2018) and can be found on all continents, except in Antarctica (Bertani 2001, West et al 2008, Perafán et al 2016. The genus Theraphosa Thorell, 1870, is represented by only 3 species: Theraphosa apophysis (Tinter ,1991), Theraphosa blondi (Latreille, 1804), and Theraphosa stirmi Rudloff & Weinmann, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of the genera are described from Latin America and the phylogeny of this group, especially the subfamily Theraphosinae, is still a subject of research because of their high biogeographical diversity and morphological variability (Pérez-Miles et al 1996;West et al 2008;Bertani 2012;Guadanucci 2014;Perafán et al 2016;Turner et al 2017). …”
Section: Introductionmentioning
confidence: 99%